INTERPRETASI MAKANAN DAN MINUMAN: Analisis Wacana Kritis Teun Van Dijk dalam Tafsir Ilmi Kemenag RI Tahun 2013 - Ita Rodiah; Imam Syafi'i (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
Al-Qur’an interpretation treasury and history in Indonesia was started by the Muslim intellectuals since the 17th century. An interpretation book is created not only to understand and explain the Qur’anic verses that are difficult to be understood. But, on the other side, turns out that mufassir who interpretates the Qur’an also explains the dialectics and reality of what is happening through text narration interpretation, until it could affect the reader’s understanding and create new discourse. This research is a library based research using Teun Van Dijk’s critical discourse analysis method. The result of this research is that “Tafsir Ilmi: Makanan dan Minuman dalam Perspektif Al-Qur’an dan Sains” was written collectively with Republic of Indonesia’s Ministry of Religion’s affiliations with shared mission and goal to succeed the government’s program of halal certification as the basis and main option for consumers to choose a product and as a discourse to obligate businesses to certify their products.